2009
DOI: 10.1021/tx9002726
|View full text |Cite
|
Sign up to set email alerts
|

Metal Allergy—A Review on Exposures, Penetration, Genetics, Prevalence, and Clinical Implications

Abstract: The prevalence of metal allergy is high in the general population, and it is estimated that up to 17% of women and 3% of men are allergic to nickel and that 1-3% are allergic to cobalt and chromium. Among dermatitis patients, the prevalence of metal allergy is even higher. Metal allergy is mainly an environmental disorder although null mutations in the filaggrin gene complex were recently found to be associated with nickel allergy and dermatitis. Environmental metal exposures include jewelry, buttons, clothing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
250
1
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(274 citation statements)
references
References 191 publications
6
250
1
17
Order By: Relevance
“…The contact or oral exposure to nickel metal or Ni(II) salts causes allergy in sensitized individuals. Also in this case, the soluble Ni(II) species are thought to be the toxic agents [120,121]. Implants made of alloys containing nickel, such as stainless steel, give rise to both types of nickel toxicity by means of a slow release of Ni(II) ions [122,123].…”
Section: Toxicological Implications Of Metal Assisted Peptide Bond Hymentioning
confidence: 99%
“…The contact or oral exposure to nickel metal or Ni(II) salts causes allergy in sensitized individuals. Also in this case, the soluble Ni(II) species are thought to be the toxic agents [120,121]. Implants made of alloys containing nickel, such as stainless steel, give rise to both types of nickel toxicity by means of a slow release of Ni(II) ions [122,123].…”
Section: Toxicological Implications Of Metal Assisted Peptide Bond Hymentioning
confidence: 99%
“…It can be found in jewelry, metal buttons, zippers, glasses frames, coins, metal parts of watches, belt buckles and mobile phones [17]. In 1994 the European Union issued a decree specifying the limits of nickel excretion by items that have direct contact with human skin at 0.5 μg/cm 2 /week.…”
Section: Contact Hypersensitivity To Nickelmentioning
confidence: 99%
“…In spite of these precautions, nickel remains the most common contact allergen in the European population. It is responsible for ACD in 65 million people [17,18] -17% of women and 3% of men [19]. Risk of hypersensitivity development is increased when direct exposure to the hapten occurs within skin deprived of an epithelial barrier.…”
Section: Contact Hypersensitivity To Nickelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted on rats and rabbits have shown that palladium has toxic effects on the kidney (14,15), liver (16,17), produces de terioration of the general condition of experimental animals (2,18) and could cause allergy in animals (14,(19)(20)(21) and humans (22)(23)(24)(25)(26). Clinical signs of acute poisoning include death, tonic and clonic convulsions, ataxia, tiptoe gait, reduced intake of food and water, weakness and abdominal distension in animals (2,18).…”
Section: Introductionmentioning
confidence: 99%